Développement d’un glossaire Français de l’Hôtellerie et de la Restauration basés sur Android Studio - Yoas Benyamin Hutauruk, Sopar; Ratna Soraya, Tengku (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This research aims to develop a glossary application using Android Studio software as part of a French Hospitality and Catering course that contains French vocabulary, instructions, explanations, images, and audio for sixth-semester students at the Unimed French section and to determine the feasibility level of the learning media developed. This research uses a Research and Development (R&D) method, Sugiyono’s development model, which comprises five stages: determining potential and problems, collecting data, product design, expert validation, and design review. The product of this research is an electronic copy containing 79 French hotel and restaurant vocabulary words. This research began with information gathering and community needs analysis, designing and creating educational materials, and validating with materials and media experts. The data collection instrument used in this research was percentage analysis. The validation results by materials experts were 92.5%, while media experts were 90.62%. The material validation results are in the “excellent” category, and the media validation results are in the “excellent” category. Therefore, the learning media developed using Android Studio are valid for learning French in the hotel and catering sector.